Sex dimorphism of VO2max trainability: A systematic review and meta-analysis - Diaz-Canestro, C.; Montero, D. (Sports Medicine, 2019)
Background: Increases in maximal oxygen uptake (VO2max) are strongly associated with improved cardiovascular health. Objective: The aim was to perform a systematic review and meta-analysis to determine whether VO2max responses to endurance training (ET), the most effective intervention to improve VO2max, are influenced by sex. Methods: We conducted a systematic search of MEDLINE and Web of Science since their inceptions until February 2019 for articles assessing the VO2max response to a given sex-matched dose of ET in healthy age-matched men and women. Meta-analyses were performed to determine the mean difference between VO2max responses in men versus women. Subgroup and meta-regression analyses were used to assess potential moderating factors. Results: After systematic review, eight studies met the inclusion criteria. All studies implemented common modalities of ET in healthy untrained individuals, comprising a total of 175 men and women (90 male, 85 female). ET duration and intensity were sex-matched in all studies. After data pooling, ET induced substantially larger increases in absolute VO2max in men compared with women (mean difference = + 191 ml·min-1, 95% CI 99, 283; P < 0.001). A greater effect of ET on relative VO2max was also observed in men versus women (mean difference = + 1.95 ml·min-1·kg-1, 95% CI 0.76, 3.15; P = 0.001). No heterogeneity was detected among studies (I2 = 0%, P = 0.59); the meta-analytical results were robust to potential moderating factors. Conclusion: Pooled evidence demonstrates greater improvements in VO2max in healthy men compared with women in response to a given dose of ET, suggesting the presence of sexual dimorphism in the trainability of aerobic capacity.